The Time over the time: reflections on the challenges of contemporary society - Díaz Müller, Luis T. (Revista Tribuna Internacional, 2014)
In this essay, the author reflects about the development of international society that has been created until our days, highlighting how the two world wars of the twentieth century, the Cold War, the fall of the Berlin Wall and finally the Wall Street crisis of 2008 have shaped our contemporary reality. The occurring processes have impacted on the concept of sovereignty as a core element of national states, with implications from the treatment given to human rights to how global markets operate. The author expresses his opinion about these challenges in our society.